Polens zentrale Zensurbehörde und die deutschsprachige Literatur 1945-1956 - Brzezińska, Bogna (Studia Germanica Posnaniensia, 2018)
GUKPPiW (Chief Control Office of Press, Publications and Shows) was established in 1946. Since that time a regular control of the German language publications took place. Therefore until 1953 the pieces wich were published in Poland included almost exclusively works of authors from the territory of the German Democratic Republic. For each edition of works for publication so called ,,reviews“ were prepared wich pinpointed any possible ideological imperfections. Finally they might approve a piece of literature, stop its publications or demand to remove certain sections. The most im important criterion used by the Office was the authors attitude towards the regime, ideological-political value of the pieces an its educational and didactical usefulness.